Hygro-thermally induced stress intensity factor of an edge crack piezo laminated composite plate. Issue 6 (4th November 2019) - Lal, Achchhe; Jain, Khushbu
Abstract : Purpose: The purpose of this paper is to evaluate hygro-thermo-mechanically induced normalized stress intensity factor (NSIF) of an edge crack symmetric angle-ply piezo laminated composite plate (PLCP) using displacement correlation method. Design/methodology/approach: In the present work, the governing equations are solved through conventional finite element method combined with higher order shear deformation plate theory utilizing the micromechanical approach. Findings: The effects of crack length, the thickness of the plate and piezoelectric layer, stacking sequences, fiber volume fraction, position of piezoelectric layer, change in moisture and temperature, and voltage on the NSIF are examined. The numerical results are presented in the form of a table for the better understanding and accuracy. The present outlined approach is validated with results available in the literature. These results can become a benchmark for future studies. Research limitations/implications: The mathematical models theoretically have been developed by considering different parameters. The results are generated using MATLAB 2015 software developed by the authors' side. Originality/value: The fracture analysis of a single edge crack PLCP with the effect of a piezoelectric layer at the different location of cracked structures, plate thickness, and actuator voltage and hygro-thermo loading is the novelty of research for health monitoring and high-performance analysis.